PENGEMBANGAN MODEL PEMBELAJARAN BULUTANGKIS MELALUI PERMAINAN LINTON BAGI SISWA KELAS IV SD NEGERI 01 RINGIN KABUPATEN REMBANG TAHUN AJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of the study resulted in a model of learning for students of classes IV badminton school year 2012-2013. Development of research methods (research-based devolepment) of Brog and Gall modified the conduct preliminary research and collect information, including field observations and literature review, developed the initial product (game model linton), expert evaluation using expert penjas and learning experts, the test group small using questionnaires and analyzed, the first product revision, the revision of the product and test results of an expert evaluation of a small group of 10 students. Revision is used for the initial product improvements are made to researchers, field testing 30 students, revision of the final product based on the results of field tests conducted, the results of the final model of learning through play badminton generated through revision modified field test. The data collection questionnaire and observation expert evaluation, test a small group of 10 students, 30 students field test. The results of the development of expert evaluation criteria penjas obtained 72% good, 80% learning experts I either category, a category II, 84% good, test a small group obtained 81.33% either category, 87.77% field tests either category, field test observations affective 87.6% of students either category. The results of field tests of psychomotor observations 80.58% of students either category. Conclusion that the model of learning through play badminton linton fourth grade students of SD Negeri 01 Ringin well, achieving an average of 81.61% so the learning development of badminton can be used as a learning penjas teacher fourth grade student Ringin District 01 State Apex.